POTENSI PENERIMAAN PAJAK - Nizar, Muhammad Afdi; Purnomo, Kuntarto (Jurnal Kajian Ekonomi dan Keuangan, 2011)
This study aims to estimate the size of underground economy activities in Indonesia. Based on the results of these estimates, further calculated the potential tax loss due to the existence of underground economy activities. This study was conducted using quantitative approaches, namely currency demand model which is estimated by ordinary least square (OLS) method. By using time series (quarterly) data period 2000 - 2009 we found that the size of underground economy is about Rpl64, 4 trillion per year on average, equivalent to 6% of GDP. Meanwhile, the potential tax loss due to the activity estimated at Rp20,6 trillion on average per year, or approximately 0.69% of GDP.